A systematic review and meta-analysis of patient activation in people living with chronic conditions. Issue 9 (September 2021) - Cuevas, Heather; Heitkemper, Elizabeth; Huang, Ya-Ching; Jang, Dong Eun; García, Alexandra A.; Zuñiga, Julie A.
Highlights: Increased patient activation is associated with appropriate use of the health care system and improved self-management. Subgroup analyses revealed that improvements in patient activation were more likely if the intervention included an interdisciplinary team. Due to heterogeneity, the meta-analysis did not corroborate the findings of the information synthesized from the articles. Patient activation interventions should be tailored to the level of patient activation to improve patient engagement in care. Abstract: Objective: The objectives of this review are to (1) describe the state of the science of patient activation interventions for the self-management of chronic conditions; (2) identify effective intervention elements for improving patient activation; and (3) compare intervention effectiveness across chronic conditions. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA). PubMed, CINAHL, and Web of Science databases were searched. Results: Thirty-two articles published between 2005 and 2019 were identified with intervention elements of self-management, disease management, and education. Meta-analysis of a subset of seven randomized controlled trials (n = 7) that used the 13-item version of the Patient Activation Measure with data collection points at 6 months demonstrated that patient activation did not change significantly in comparison with controls (MD = 0.25, 95 % CI = 0.02–0.47). Conclusion: Most interventions reported significant improvement in patient activation and were linked to tasks such as regular exercise and monitoring glucose. However, the meta-analysis of RCTs did not confirm these findings. Practice implications: Patient activation can be assessed and addressed uniformly across all chronic conditions to improve patient engagement in care.